Damage detection and full surface characterization of a wind turbine blade using three-dimensional digital image correlation. (September 2013) - LeBlanc, Bruce; Niezrecki, Christopher; Avitabile, Peter; Chen, Julie; Sherwood, James
The increasing demand for wind power has led to a significant increase in the number and size of wind turbine blades manufactured globally. As the number and physical size of turbines deployed grow, the probability of manufacturing defects being present in composite turbine blades also increases. As capital blade costs and operational and maintenance expenses increase in ever larger turbine systems, the need for inspection of the structural health of large-scale turbine blades during operation critically increases. One method for locating and quantifying manufacturing defects, while also allowing for the in situ measurement of the structural health of blades, is monitoring the full-field deformation and strain of a blade. In a demonstration of this methodology, static tests were performed on a Sandia National Laboratories CX-100 9-m composite turbine blade to extract full-field displacement and strain measurements. Three-dimensional digital image correlation was used. Measurements were taken at previously identified damaged areas near the blade root, along the high- and low-pressure surfaces. The results indicate that the measurement approach can clearly identify failure locations and discontinuities in the blade curvature under load. Postprocessing of the data, using a stitching technique of digital image correlation snapshots taken along the length of the blade, allows observation of the shape and curvature of the entire blade. The experiment demonstrates the feasibility of the approach and reveals that the technique can be readily scaled to accommodate utility-scale blades. As long as a trackable pattern is applied to the surface of the blade, measurements can be made in situ when a blade is on a manufacturing floor, installed in a test fixture, or installed on a rotating turbine. The results demonstrate the potential of the optical measurement technique for use in the wind industry.